Lire les techniques pour comprendre les rapports entre humains et non-humains - Nastassia Reyes (Revue d'ethnoécologie)
The ethnoecological approach provides a complex framework to address the relationship between humans and the environment. It opens the way to a detailed understanding of the practices, uses and representations of the actors. This reveals how the different elements of a technical tool, in fishing for case in point, are related to the characteristics and behaviours of the target animal. Rather than an analysis based essentially on the material dimension, this proposal insists on the changeable and seasonal dimension of practices, and on the understanding acquired by the fisherman about the fish. I intend to follow, as a reflexive chronicle, the conceptual and methodological process undertaken during the surveys conducted among artisan fishermen in the northern Mediterranean area. A focus will be placed on the environmental practices and knowledge of the fishermen of Catania (Sicily). I will discuss in detail the contributions and limitations that I was confronted with throughout the data collection work, and I will make proposals for an analysis of the knowledge and practices that is devoid of the incompleteness inherent in the understanding of environmental knowledge. On the one hand, this proposal aims to report on the techniques with a level of finesse that makes sense for the fishermen, and on the other hand, on the intimate links between human and non-human actors - in this case the fisherman and the fish - in the fishing practice.